Analisa Kekuatan Rangka pada Traktor - Cahyo Budi Nugroho (JURNAL INTEGRASI, 2015)
Tractor is tool help in horticultural effort that helps farmers, to soften work that is done in process losen earth for agricultural farm. Bulldoze this hand is a usufruct from Polytechnic college student to prop requirement in world agricultural. To the effect of observational it is subject to be know how big charges of frame force bulldoze Tembesi. Method that at utilizes is morphological by use of software solid work, two charges that at accepts by hand's frame bulldozes consisting of machine which lie at frontage (21Kg) and pulley’s system (9Kg). For it to usufruct from this research is on charges 210N stress's zooms is contemned with point 21.4 N/mm2, and beginning part strikes stress's impact by assesses 8.212 N/mm2, stress's appreciative zoom supreme with point 12.318 N/mm2, and on charges examination 90N stress's zooms is contemned with point 14.2 N/mm2, and beginning part strikes stress's impact by assesses 2.731 N/mm2, stress's appreciative zoom supreme with point 4.096 N/mm2.